Implementasi Sistem Pemesanan Produk Berbasis Android (Studi Kasus: Pangestu Catering & Cafe) - Eva, Lidya Nurmala; Retnowo, Murti (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2024)
Pangestu Catering & Caffe is a place that many people visit to have fun, hang out or do work. Ordering and transaction processes at Pangestu Catering & Caffe are always done manually. Diners come later and order the menu. The cashier will then record guest orders manually and then hand them over to the kitchen. However, this becomes inefficient due to the accumulation of queues. To overcome this queue problem, a product ordering system is needed that can facilitate recording of transactions and can be integrated into the system. The author implements a product ordering system that customers use to order food menus and then submit the receipt to the cashier for payment. After payment, the order will be processed by the kitchen. The Android-based product ordering system uses the prototype development model and the Flutter dart language.